Progress in brain research - Pompeiano, O.; Allum, J. H. J. (Progress in brain research, 1988)
This volume publishes the review articles presented by the invited speakers at the Satellite Meeting to the Barany Society Meeting held in Bologna, Italy during June 1987. The subject matter in this book is divided into seven main sections. The first three present basic neuroanatomical and neurophysiological aspects of vestibulospinal reflexes and document the neck afferent and visual influences on these reflexes. The following sections deal with the control of locomotion, posture, and eye-head-trunk coordination by vestibulospinal signals. The final section provides current knowledge on the processes underlying compensation of vestibulospinal deficits. An overall review precedes each main section so that the reader is informed as to which questions are still controversial and require further investigation. In this way a basis is provided for those needing a current account of the field of vestibulospinal reflexes. Due to the extensive length of the contents, only the number of articles presented per session is listed below.